Respuesta :

Steps Using Factoring By Grouping

[tex]4 {s}^{2} - 12s = - 9[/tex]

[tex]4 {s}^{2} - 12s + 9 = 0[/tex]

[tex](4 {s}^{2} - 6s) + ( - 6s + 9) = 0[/tex]

[tex]2s(2s - 3) - 3(2s - 3) = 0[/tex]

[tex](2s - 3)(2s - 3) = 0[/tex]

[tex](2s - 3) {}^{2} = 0[/tex]

 ‍ 

[tex]2 s - 3 = 0[/tex]

[tex] \: \: \: \: \: \: \: 2s = 0 + 3[/tex]

[tex] \: \: \: \: \: \: \: 2s = 3[/tex]

[tex] \: \: \: \: \: \: \: \: \: s = \frac{3}{2} [/tex]

[tex] \: \: \: \: \: \: \: \: \: s = 1 \frac{1}{2} [/tex]

[tex] \: \: \: \: \: \: \: \: \: s = 1,5[/tex]

[tex] \green {\boxed{s = \frac{3}{2} = 1 \frac{1}{2} =1,5}}[/tex]

#IfWrongPleaseReport

#StudyTogetherWithMe

#ILoveMath

ACCESS MORE